Потери в частотно-управляемом асинхронном двигателе при различных законах регулирования и типах преобразователей частоты - Осташевский, Николай Александрович; Иваненко, Виталий Никитович; Петренко, Александр Николаевич (НТУ "ХПИ", 2009)
В статье рассмотрена и проанализирована специфика расчета потерь в частотно-управляемом асинхронном двигателе при различных законах регулирования (закон пропорционального регулирования, закон квадратичного регулирования, закон регулирования при постоянной мощности).

Losses in a frequency-controlled asynchronous motor under different laws of control and types of frequency converters. The paper considers and analyzes specificity of calculation of losses in a frequency-controlled asynchronous motor under different laws of control, namely, law of proportional control, law of quadratic control, law of control under sustained power.
Losses in a frequency-controlled asynchronous motor under different laws of control and types of frequency converters
Keywords: магнитный поток; перегрузочная способность; электромагнитный момент; нагрузка; frequency-controlled asynchronous motor; laws of control; losses; calculation